Out of school children in the tea gardens and ethnic minority communities - Nath, Samir Ranjan; Yasmin, Rosie Nilufar; Shahjamal, Mirja M (BRAC Research and Evaluation Division (RED), 2019)
Although many countries in the world have moved from compulsory primary education to compulsory secondary education and many increased the duration of primary and basic education from 4-5 years to more than six years, Bangladesh is still dealing with five years compulsory primary education. However, the strong commitment of the nation, has resulted in a gradual improvement in the situation regarding access to primary education and completing the full course. The improvements accelerated after the Jomtien initiative, where Bangladesh rightly responded to the international call for basic and primary education for all. Some affirmative actions taken by both the government and the non-governmental organisations made this improvement possible. However, at present, one in every five of the 6- I 5 years old children is out of school and nearly 30% of the enrolled children leave school before completing the full course of primary education. Gender parity, at the aggregate level, has been achieved in access to primary schooling. Tn spite of this scenario of hope at the national level, it has been noticed that the improvements have not been distributed equally among all sections of the population. There is urban-rural as well as district-wise variation. Other research on poverty and education show that the worst situation exists in char lands, the tea gardens, ethnic minorities, people living in extreme poverty, street children, the disabled, domestic workers, children working in factories, children in jails and brothels, and those involved in crime. In order to achieve the educational goals of the MDGs (Millennium Development Goals) we must take care of the schooling of the children of above-mentioned groups. However, no study has looked deeply at each of the groups. This study for the first time looks at the situation of the out of school children in two sub-groups of population in Bangladesh. These are the people living in the tea gardens and the ethnic minorities in the country. Emphasis was given on estimating the volume of out of school children in the groups and their socioeconomic status, their workload at home and outside, and the ways they can be put back to school.